(untitled) (Ameghiniana, 2013)
Abstract. About 100 specimens of the stem-anuran Notobatrachusdegiustoi, from several localities of the Middle-Late Jurassic La Matilde Formation of southern Patagonia, were examined. This was aimed at clarifying numerous controversial aspects of its anatomy and executing an updated restoration of its skeleton, presented herein. Additionally, the few available immature specimens provide some data on the osteogenesis of this evolutionarily significant taxon. This study also revealed variation in the morphology of the adult sacral region, this variation being more evident among the specimens from one of the localities. Resumen. UNA NUEVA MIRADA A UNA ANTIGUA RANA: NOTOBATRACHUS REIG DEL JURÁSICO DE PATAGONIA. Fueron examinados alrededor de 100 ejemplares del stem-anuro Notobatrachusdegiustoi provenientes de varias localidades de la Formación La Matilde (Jurásico Medio-Superior) en el extremo sur de Patagonia. Este análisis tuvo como objetivo clarificar numerosos aspectos controvertidos de su anatomía y elaborar una reconstrucción actualizada de su esqueleto, presentada aquí. Además, los pocos especímenes inmaduros disponibles proveyeron datos acerca de la osteogénesis de este taxón evolutivamente significativo. Este estudio reveló también variación en la morfología adulta de la región sacra, siendo esta variación más evidente entre los ejemplares provenientes de una de las localidades.